Cellular Automata and Discrete Complex Systems: 20th International Workshop, AUTOMATA 2014, Himeji, Japan, July 7-9, 2014, Revised Selected Papers - Isokawa, T (Springer, 2015)
This book constitutes revised selected papers from the 20th International Workshop on Cellular Automata and Discrete Complex Systems, AUTOMATA 2014, held in Himeji, Japan, in July 2014.